2024
DOI: 10.3389/fvets.2023.1328698
|View full text |Cite
|
Sign up to set email alerts
|

Drug prescription pattern in exotic pet and wildlife animal practice: a retrospective study in a Spanish veterinary teaching hospital from 2018 to 2022

Beatriz Romero,
Julen Susperregui,
Ana M. Sahagún
et al.

Abstract: Exotic companion animals have had an important role in our society since ancient times. Preserving animal health is necessary to do a responsible use of veterinary medicines. This study aimed to describe the prescription patterns of drugs in exotic pets and wildlife animals attending the Veterinary Teaching Hospital of the University of León (HVULE). A retrospective study was carried out between 2018 and 2022. Birds were the largest group of exotic animals attending the HVULE. Visits were related to emergency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Despite pet ownership being common worldwide, with almost half of European households possessing at least one companion animal, 15.7% of which are birds (the largest group of exotic animals in Europe), awareness of the risks that such close contact with family members pose, especially to immunocompromised people, is not always taken seriously [ 73 , 74 ]. One study demonstrated that even some medical professionals are not aware of the zoonotic risks associated with keeping a pet bird, neglecting important and common zoonotic events, such as the previously mentioned salmonellosis and psittacosis [ 73 ].…”
Section: Pet Birds As Reservoirs Of Resistant and Zoonotic Bacteriamentioning
confidence: 99%
“…Despite pet ownership being common worldwide, with almost half of European households possessing at least one companion animal, 15.7% of which are birds (the largest group of exotic animals in Europe), awareness of the risks that such close contact with family members pose, especially to immunocompromised people, is not always taken seriously [ 73 , 74 ]. One study demonstrated that even some medical professionals are not aware of the zoonotic risks associated with keeping a pet bird, neglecting important and common zoonotic events, such as the previously mentioned salmonellosis and psittacosis [ 73 ].…”
Section: Pet Birds As Reservoirs Of Resistant and Zoonotic Bacteriamentioning
confidence: 99%